Relationship between Tirso de Molina and Lope de Vega: An approach to the literature review - Loeza Zaldivar, Alejandro (2018)
This paper presents a chronology of the relationship between Tirso de Molina and Lope de Vega. The reasons and factors under which this relationship is still an interpretation based on circumstances is through the chronology of their works and the critical analysis of leading tirsistas. This paper is a review of that relationship through the works, dedications, laudatory of writers.